2019
DOI: 10.1002/mp.13404
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Relative proton stopping power estimation from virtual monoenergetic images reconstructed from dual‐layer computed tomography

Abstract: Purpose: The objective of this technical note was to investigate the accuracy of proton stopping power relative to water (RSP) estimation using a novel dual-layer, dual-energy computed tomography (DL-DECT) scanner for potential use in proton therapy planning. DL-DECT allows dual-energy reconstruction from scans acquired at a single x-ray tube voltage V by using two-layered detectors. Methods: Sets of calibration and evaluation inserts were scanned at a DL-DECT scanner in a custom phantom with variable diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…We have demonstrated that the proposed method can predict SPRs with an accuracy that, for soft tissue and bone, matches or improves on the SPRs predicted with the conventional stoichiometric method. While no direct comparison could be made to other DECT‐based methods for SPR prediction, as we found no such method that could be implemented on a fast kV‐switching system, the SPR RMSEs for soft tissue and bone in Table 4 are comparable with RMSEs reported in the literature 21‐23 …”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…We have demonstrated that the proposed method can predict SPRs with an accuracy that, for soft tissue and bone, matches or improves on the SPRs predicted with the conventional stoichiometric method. While no direct comparison could be made to other DECT‐based methods for SPR prediction, as we found no such method that could be implemented on a fast kV‐switching system, the SPR RMSEs for soft tissue and bone in Table 4 are comparable with RMSEs reported in the literature 21‐23 …”
Section: Discussionmentioning
confidence: 58%
“…Landry et al adapted the work of Hudobivnik et al for a dual-layer DECT reporting a SPR RMSE <0.8%, and Faller et al evaluated the built-in applications for extracting EAN and RED on the same type of DECT make and model, reporting a SPR RMSE <0.6%. [21][22][23] We have not found any consensus in the literature, or in clinical codes of practice, regarding which method would constitute the best approach.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations